Glaucoma Surgery Treatment and Techniques (Springer International Publishing, 2018)
This book illustrates effective surgical techniques for treating glaucoma in a practical and easy to follow format. Within the various chapters the different steps for all surgical procedures are clearly described to guide the reader through each clinical presentation. There are many drawings with detailed explanations regarding incisional surgical techniques such as trabeculectomy, shunts and non perforating techniques, canaloplasty and modern Microinvasive Glaucoma Surgeries (MIGSs). Surgical anatomy, different anesthetic techniques, medical therapy, laser treatments and choice of treatment to contrast glaucoma are also explained throughout the book. Finally there are three chapters on the most modern and effective surgical procedures, drawn up by leading internationally renowned ophthalmologists. This book will be an essential clinical resource for a wide range of readers including ophthalmologists in training, experienced surgeons and glaucoma specialists. .